Liraglutide protects pancreatic beta cells during an early intervention in Gato‐Kakizaki rats (Gato‐Kakizaki大鼠使用利拉鲁肽进行早期干预可以保护胰腺β细胞). (4th June 2013) - Luo, Xiu; Pan, Linlin; Nie, Aifang; Wang, Qidi; Gu, Yanyun; Li, Fengying; Zhang, Hongli; Li, Wenyi; Li, Xiaoying
Abstract: Background: Glucagon‐like peptide‐1 (GLP‐1) analogues have emerged as insulin secretagogues and are widely used in type 2 diabetic patients. GLP‐1 analogues also demonstrate a promotion of beta cell proliferation and reduction of apoptosis in rodents. In the present study, we investigated the protection of pancreatic beta cells by early use (at the age of 2 weeks) of GLP‐1 analogue, liraglutide in Gato‐Kakizaki (GK) rats and explored the underlying mechanisms. Methods: The effects of liraglutide on glucose tolerance were evaluated by intraperitoneal glucose tolerance test (IPGTT) and insulin release tests (IRT). Ki67 and terminal deoxynucleotidyl transferase‐mediated dUTP nick end labeling (TUNEL) immunostaining, Western blots and real‐time polymerase chain reaction were applied to evaluate cell proliferation, apoptosis and related gene expressions. Results: Our results demonstrated that early use of liraglutide improved glucose tolerance during liraglutide treatment in GK rats. Liraglutide increased pancreatic insulin contents and markedly reduced beta cell apoptosis. Liraglutide also downregulated pro‐apoptotic gene expressions and reduced intra‐islet macrophage infiltration. Conclusions: This experiment reported for the first time that early use of liraglutide could protect beta cell failure in pre‐diabetic GK rats through reduction of beta cell apoptosis and ameliorating islet inflammation.